Odpowiedź :
a) -4(2x+0,5)=-8x-2
b) 3(x²-2) - (5-6²)=3x²-6-5+36=3x²+25
c) -3(1-2y) + ½(6-12y)=-3+6y+3-6y=0
d) -(x-2) - 4(½-x)=-x+2-2+x=0
:) prosze
b) 3(x²-2) - (5-6²)=3x²-6-5+36=3x²+25
c) -3(1-2y) + ½(6-12y)=-3+6y+3-6y=0
d) -(x-2) - 4(½-x)=-x+2-2+x=0
:) prosze
Zapisz w jak najprostszej postaci
a) -4(2x+0,5)=-8x-2
b) 3(x²-2) - (5-6x²)=3x²-6-5+6x²=9x²-11
c) -3(1-2y) + ½(6-12y)=-3+6y+3 -6y=0
d) -(x-2) - 4(½-x)=-x+2-2+4x=3x
a) -4(2x+0,5)=-8x-2
b) 3(x²-2) - (5-6x²)=3x²-6-5+6x²=9x²-11
c) -3(1-2y) + ½(6-12y)=-3+6y+3 -6y=0
d) -(x-2) - 4(½-x)=-x+2-2+4x=3x